Evaluation of coastal hydrodynamic performance using statistical analysis at the Kelantan coast, Malaysia - Nurul A’idah Abd Rahim,; Khairul Nizam Abdul Maulud,; Fazly Amri Mohd,; Lee, Hin Lee; Wan Hanna Melini Wan Mohtar, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Coastal zones are vulnerable to the effects of nature and man, as well as being physically volatile. The interaction of hydrodynamic conditions in coastal areas is a complex phenomenon. Considering the characteristics in this specific area, understanding its hydrodynamic behaviour should be obviously clarified. Thus, the hydrodynamic characteristics for Kelantan coast had been simulated using a numerical software of MIKE 21 Hydrodynamic FM. To assess the performance of the model, a combination of time series analysis and statistical evaluation were carried out against two weeks of observed data. Time series analysis shows a good agreement with the field measurements for both magnitude and phase. Statistical analysis using Root Mean Squared Errors (RMSE) and Regression analysis (R2) for current speed and water level were analysed. The results indicate that the RMSE for current speed are 8.97% and 8.00% for ADCP 1 and ADCP 2, respectively while the RMSE for water level is 8.89 %. Through the regression analysis, the output indicates that the numerical model is in a good performance as the R2 ranged from 0.72 to 0.9. Both time series and statistical approach were successfully utilised in the hydrodynamic model to determine the performance of the coastal hydrodynamic characteristics in Kelantan’s coastline. The output model can provide important information, especially on the coastal management and land-use planning for the developers, planners and state authority.